DARK HORIZONS: IDENTIFYING AND LEVERAGING MICRO-NICHES IN DARK TOURISM - Wei, Liang Jun; Fang, Chen Xiao (International Research Journal of Arts and Communication, 2024)
The concept of "dark tourism" encompasses the phenomenon of individuals being drawn to sites associated with death, disaster, and suffering, sparking travel interests. Recent years have witnessed a surge in public health crises, extreme natural calamities, and malevolent human acts around the world. These events, while causing profound human and economic losses, have endowed us with invaluable resources for dark tourism. Brown (2013) offered an expansive definition of dark tourist destinations, encapsulating them as "locations linked to death, pain, and tragic events." Consequently, numerous sites globally can be categorized as providers of dark tourism experiences. These dark tourist attractions not only serve as tangible repositories of historical lessons but also carry collective and individual memories of calamities. An increasing number of tourists seek to engage with the tension and emotional gratification associated with death through dark tourism. Thus, there is a critical need to accurately position and chart the future development of this distinct niche in the field of tourism.